EFEKTIVITAS PENGAWASAN KOMISI YUDISIAL PENGHUBUNG WILAYAH RIAU TERHADAP PENEGAKAN KODE ETIK HAKIM DI PENGADILAN NEGERI PEKANBARU TAHUN 2021 - Muhammad Roif Alghani; Dodi Haryono; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Judicial Commission Liaison (PKY) is an institution that assists the tasks ofthe Indonesian Judicial Commission in the regions. PKY Riau Region was formedin 2013, according to Judicial Commission Regulation Number 1 of 2012concerning the Establishment, Structure and Liaison Work Procedures forRegional Judicial Commissions, its performance has not been optimal in carryingout its duties and functions.The method used study is an empirical juridicalapproach or legal sociology. The author conducted direct research at the researchlocations at the Riau Region PKY Office and the Pekanbaru District Court. Thesampling technique was total sampling. Primary data collection by interviews,observation and documentation, while secondary data by way of literature study.Furthermore, all data is processed and studied using a descriptive analyticalmethod that combines field data with library data.The results of the study show thatthe Riau Regional PKY in carrying out the task of maintaining the honor andnobility, dignity and behavior of judges is based on public reports while sanctionsagainst judges for violations are the authority of the Indonesian JudicialCommission (central). There are several inhibiting factors that affect theperformance of the Riau Region PKY in enforcing the Code of Ethics for Judges atthe Pekanbaru District Court, including online trials, covid-19, lack of humanresources, and limited authority. This causes the supervision carried out by theRiau Region PKY to enforce the Code of Ethics for Judges at the Pekanbaru DistrictCourt in 2021 to be less effectiveKeywords: Judicial Commission, Judicial Commission Liaison, Enforcement ofthe Code of Ethics and Judges Code of Conduct,